miR-19a-3p Promotes Tumor-Relevant Behaviors in Bladder Urothelial Carcinoma via Targeting THBS1 - Gang Xu (Hindawi Limited, 2021)
Objective. miR-19a-3p is widely increased in several cancers and can be used as an oncogenic factor in these cancers. However, the molecular mechanism of miR-19a-3p in bladder urothelial carcinoma (BLCA) is still open. So, the study was aimed at exploring the mechanism of miR-19a-3p in BLCA cells. Methods. Bioinformatics analysis was employed to find the differential miRNAs and mRNAs, and the target miRNA and mRNA were determined. Real-time quantitative PCR was used to evaluate miR-19a-3p and THBS1 levels in human urethral epithelial cells and BLCA cells. Western blot was carried out to assay protein expression of THBS1 in human urethral epithelial cells and BLCA cells. Behaviors of BLCA cells were detected through cellular functional assays. Dual-luciferase gene assay was conducted to validate the binding of miR-19a-3p and THBS1. Results. miR-19a-3p was increased in BLCA cells, while THBS1 was less expressed in BLCA cells. The miR-19a-3p functions as an oncogene in BLCA. THBS1 was a target of miR-19a-3p, and it could reverse the promotion of miR-19a-3p on cell malignant behaviors in BLCA. Conclusion. miR-19a-3p facilitates cell progression in BLCA via binding THBS1, which may be an underlying therapeutic target for BLCA treatment.